Status of Patient Flow in the Emergency Department of Kathmandu Medical College Before and After the National Level Lockdown for Pandemic - Pant, Manish Nath; Ranjitkar, Neeti; Khanal, Tulsi Raj; Singh, Bishnu (Journal of Karnali Academy of Health Sciences, 2020)
Background: Emergency visits during pandemic also comprise patients with various complains other than symptoms of COVID. It is prudent to identify variation of non- COVID-19 cases that visit emergency department during pandemic and their outcome for proper division of resources including human resources during pandemic.Methods: This is a cross sectional study done in emergency department of Kathmandu Medical College Teaching Hospital  Data were collected from the record book from 24th March 2020 to 21st July 2020 and four months prior to 24th March. The variation in emergency admissions, demographic profile, outcome of the patients, departments admitting the patients and place of admission was evaluated using SPSS.Results: Total of 6944 cases were seen during the pre-lockdown period and 2503 cases during the lockdown period, which is 63.95% less than the pre-lockdown era. Males (53.14% and 53.40% during pre-lockdown and lockdown respectively) visited emergency more frequently than females during both the periods. The number of cases that were admitted from the ER during the lockdown had fallen by 67.5% from the prelockdown era. Likewise, the patients admitted in ward, high care, ICU had decreased by 76%, 49%, 64% respectively compared to pre-lockdown period. However, the rate of admissions in intensive care unit had risen from 32.58% to 35.73% during lockdown. Conclusion: The overall rate of admissions was low both for the COVID. However, the admission in intensive care units increased during the lockdown period which gives the idea that people were only visiting hospital when their symptoms were worse.